Climate Change Determines Future Population Exposure to Summertime Compound Dry and Hot Events. Issue 11 (28th October 2022) - Zhang, Gengxi; Wang, Huimin; Gan, Thian Yew; Zhang, Shuyu; Shi, Lijie; Zhao, Jin; Su, Xiaoling; Song, Songbai
Abstract: Compound dry and hot events (CDHEs) have increased significantly and caused agricultural losses and adverse impacts on human health. It is thus critical to investigate changes in CDHEs and population exposure in responding to climate change. Based on the simulations of the Coupled Model Intercomparison Project Phase 6 (CMIP6), future changes in CDHEs and population exposure are estimated under four Shared Socioeconomic Pathways climate scenarios (SSPs) at first. And then the driving forces behind these changes are analyzed and discussed. The results show that the occurrence of CDHEs is expected to increase by larger magnitudes by the end of the 21st century (the 2080s) than that by the mid‐21st century (2050s). Correspondingly, population exposure to CDHEs is expected to increase significantly responding to higher global warming (SSP3‐7.0 and SSP5‐8.5) but is limited to a relatively low level under the modest emission scenarios (SSP1‐2.6). Globally, compared to 1985–2014, the exposure is expected to increase by 8.5 and 7.7 times under SSP3‐7.0 and SSP5‐8.5 scenarios by the 2080s, respectively. Regionally, Sahara has the largest increase in population exposure to CDHEs, followed by the Mediterranean, Northeast America, Central America, Africa, and Central Asia. The contribution of climate change to the increase of exposure is about 75% by the 2080s under the SSP5‐8.5 scenarios, while that of population change is much lower. The conclusion highlights the importance and urgency of implementing mitigation strategies to alleviate the influence of CDHEs on human society. Plain Language Summary: Under global warming, the occurrence of compound dry and hot events (CDHEs) is expected to increase, which may cause more severe damage to human society. Based on the Coupled Model Intercomparison Project Phase 6, the changes in population exposure to CDHEs and the driving forces are estimated and discussed in this study. The results show that the occurrence of CDHEs and population exposure are expected to increase substantially, especially under high‐emission scenarios. Sahara is expected to have the largest increase in population exposure to CDHEs, followed by the Mediterranean, Northeast America, Central America, Africa, and Central Asia. The influence of climate change on the increase in exposure is much larger than that of the population change. Therefore, it is important and urgent to make mitigation strategies to alleviate the impacts of CDHEs on human society. Key Points: The occurrence of summertime compound dry and hot events is projected to increase substantially over the 21st century across the globe Exposure is expected to increase significantly under SSP3‐7.0 and SSP5‐8.5 but is limited to a low level under SSP1‐2.6 scenarios Climate change determines the increase in population exposure in most regions of the world